Epidemiology and risk factor analysis of systemic allergic reaction to bee venom in the Slovenian population of beekeepers - Carli, Tanja (Zdravstveno varstvo, 2025)
Objectives: To estimate the lifetime prevalence of first and recurrent systemic allergic reaction to bee venom among Slovenian beekeepers. Additionally, we aimed to elucidate the risk factors predisposing beekeepers to developing systemic allergic reaction to bee venom. Methods: A nationwide cross-sectional study was conducted among 1,080 beekeepers who are members of the Slovenian beekeeper’s association, between 1 November 2021 and 31 May 2023. Epidemiological data were collected using a validated questionnaire, with the clinician-confirmed observed health outcome. Results: The estimated overall lifetime prevalence of self-reported first systemic allergic reaction to bee venom was 9.4% (102/1,080), with 40.7% (24/59) of the clinician-confirmed cases being severe (grade III-IV according to the Mueller classification). The estimated overall lifetime prevalence of reported recurrent systemic allergic reaction to bee venom was lower at 3.7% (40/1,080), with 60.0% (9/15) of the clinician-confirmed cases being severe (grade III-IV according to the Mueller classification). Risk factors associated with the first systemic allergic reaction to bee venom included age, male sex, number of bee stings per season, a history of large local reaction and experiencing nasal symptoms while working at hives. Younger male beekeepers, with a low number of bee stings per season, a history of large local reaction and nasal symptoms while working at hives, are at a high risk of having systemic allergic reaction to bee venom. Conclusions: High lifetime prevalence of clinician-confirmed severe first and recurrent systemic allergic reaction to bee venom underscored the importance of targeted public health strategies and clinical interventions to protect this high-risk population.
Keywords: beekeeping; čebelarjenje; javno zdravje; preobčutljivost; prevalenca; prevalence; public health; venom hypersensitivity